Immersion pulmonary oedema in a triathlete - a diagnostic challenge in sports cardiology - Sobieszek, A.; Konopka, M.; Cacko, M.; Kuch, M.; Braksator, W. (Journal of Ultrasonography, 2021)
Immersion pulmonary oedema, also referred to as swimming-induced pulmonary oedema, is a form of pulmonary oedema which usually occurs during swimming in cold water. The condition is most common in triathlon athletes; it was first reported in military divers. The main symptoms include acute dyspnoea, cough, and occasionally haemoptysis, which usually subside within approximately 48 hours. The pathomechanism is not fully understood, but oedema is suspected to be due to an increased systemic vascular resistance that overloads the left ventricle. The diagnostic process can be challenging and require multiple stages to rule out a number of other possible conditions. In view of the circumstances in which incidents typically occur, immersion pulmonary oedema poses an immediate life threat to individuals involved in selected forms of physical activity, where survival is often determined by appropriate training of medical services.